Comparison of Deep Learning and MOORA Performance Methods in Multi Criteria Decision Making with Case Studies Best public health center - Rizki Anantama; Rachmad Hidayat (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This research paper compares the performance of the deep learning and MOORA methods in making multi-criteria decisions to choose the best puskesmas. This paper discusses the methodologies used in both approaches, the architectures and equations used in deep learning, and the advantages and limitations of each method. The results show that the deep learning approach achieves 100% accuracy and the MOORA approach dss model obtains an accuracy of 95.75%.